2022
DOI: 10.1021/acsfoodscitech.1c00361
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Metal Ion in Modulating the Binding Interaction of a Dietary Flavonoid with Bovine Serum Albumin and DNA: A Spectroscopic and Theoretical Approach

Abstract: Plant-derived flavonoids are an excellent option as a potential substitute to synthetic products in food industries, and flavonoid−metal complexes exhibit better functional properties than free flavonoids. Here, an iron(II) complex of rutin, a dietary flavonoid, has been synthesized and characterized. A comparative assessment of the interaction of rutin and its iron(II) complex with the transport protein [bovine serum albumin (BSA)] and deoxyribonucleic acid (DNA) has been performed. The interaction process ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 68 publications
(140 reference statements)
0
8
0
Order By: Relevance
“…The binding constants K a = 3.2× 10 5 , 7.1 × 10 5 , and 1.1 × 10 5 L·mol –1 and the number of binding sites n = 0.9, 2.2, and 1.2for Lut, Lut–Cu­(II), and Cu­(II) with BSA, respectively, were calculated by fitting according to the double-logarithm equation as shown in Figure g–i, and the results are summarized in Table . The results meant that Cu­(II) coordination to Lut not only promoted one more Lut molecule further binding with BSA but also elevated the binding constants of Cu­(II)–Lut, ∼2.2 times of Lut, which was different from Fe­(II) coordination to rutin resulting in the decrease in binding constant and keeping mono-site binding with BSA as the parent rutin …”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The binding constants K a = 3.2× 10 5 , 7.1 × 10 5 , and 1.1 × 10 5 L·mol –1 and the number of binding sites n = 0.9, 2.2, and 1.2for Lut, Lut–Cu­(II), and Cu­(II) with BSA, respectively, were calculated by fitting according to the double-logarithm equation as shown in Figure g–i, and the results are summarized in Table . The results meant that Cu­(II) coordination to Lut not only promoted one more Lut molecule further binding with BSA but also elevated the binding constants of Cu­(II)–Lut, ∼2.2 times of Lut, which was different from Fe­(II) coordination to rutin resulting in the decrease in binding constant and keeping mono-site binding with BSA as the parent rutin …”
Section: Resultsmentioning
confidence: 94%
“…The results meant that Cu(II) coordination to Lut not only promoted one more Lut molecule further binding with BSA but also elevated the binding constants of Cu(II)−Lut, ∼2.2 times of Lut, which was different from Fe(II) coordination to rutin resulting in the decrease in binding constant and keeping mono-site binding with BSA as the parent rutin. 52 3.1.3. Site-Specific Experiments.…”
Section: Resultsmentioning
confidence: 99%
“…According to the report of Papadopoulou et al, quercetin showed a total quenching ability for the tryptophan fluorescence of BSA at a molar ratio of 10:1, whereas rutin required a molar ratio of approximately 25:1 . The presence of rutinose in rutin makes it less hydrophobic and bulkier than quercetin, increasing the steric hindrance of its penetration into the hydrophobic pocket of Trp-212 . As a result, the quenching effect of rutin on tryptophan residues was negatively affected.…”
Section: Resultsmentioning
confidence: 99%
“…34 The presence of rutinose in rutin makes it less hydrophobic and bulkier than quercetin, increasing the steric hindrance of its penetration into the hydrophobic pocket of Trp-212. 47 As a result, the quenching effect of rutin on tryptophan residues was negatively affected. The molecular docking results further support this observation.…”
Section: Effects Of Pef On the Composition Of Nf Samplesmentioning
confidence: 99%
“…The role of several drugs binding with BSA has been well explored in the literature through experimental and computational methods. These methods have provided an immense source of information regarding the bimolecular interactions, binding affinity, and binding sites that are crucial for protein–ligand interactions . Herein, we have carried out the Mol.Doc method in analyzing the binding stability and the energetics of BSA site I and BSA site II drugs.…”
Section: Resultsmentioning
confidence: 99%